Sequencing of messenger RNA in the healing process of diabetes foot ulcer - Wang, Guili; Wu, Ding; Lu, Donglin; Wu, Huifang; Cai, Yunmin; Meng, Qingyi; Liu, Zhaoxuan (Frontiers in Endocrinology, 2024)
Background: Transcriptome analysis of skin wound tissues from diabetic foot ulcer (DFU) patients to assess changes in the microenvironment during wound healing is performed by messenger RNA (mRNA) sequencing.Methods: All 5 patients with initial DFU area ≥ 3 cm 2 were selected for wound specimen collection at two time points of 0% and 50% wound healing. A total of 10 skin wound samples were obtained for mRNA sequencing. According to the sequencing results, quantitative polymerase chain reaction (qPCR) validation was performed on 12 relevant genes related to angiogenesis, fibroblast proliferation, and wound inflammation. All patients received electrospun poly (L-lactide-co-caprolactone) and formulated porcine fibrinogen (PLCL/Fg) dressing for DFU treatment.Results: The mRNA sequencing results of DFU skin specimens showed that compared to the 0% and 50% wound healing time points, there were 4347 differentially expressed genes, including 2827 upregulated genes and 1520 downregulated genes. Enrichment analysis of the differentially expressed genes using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that the upregulated genes were mainly associated with biological processes such as cell adhesion, adhesion junctions, epidermal development, and skin barrier formation. The qPCR analysis results indicated that the increased expression of fibroblast growth factor, vascular endothelial growth factor, and CD200 gene was related to DFU healing.3 Conclusion: The healing process of DFU wounds involves the interaction of multiple factors, especially in inflammation control, angiogenesis, and fibroblast proliferation.